The Contributing Factor of Depression Among Women with Infertility at the Hospital Canselor Tuanku Muhriz, Pusat Perubatan Universiti Kebangsaan Malaysia - Ismai, A’dawiyah; Razali, Nurulaneeyamirah (International Journal of Psychosocial Rehabilitation, 2020)
It is the dream of every married couple to have their own children. The instinct in wanting to become a mother is experienced by each married woman. However, due to the problem of infertility experienced by some of these women, they also suffer from emotional stress. This study aims to present the causes of emotional stress among infertile women. The design of this study is quantitative research survey. Data collection was made through the questionnaire instrument distributed to 65 infertile Muslim women who undergo fertility treatment at the Reproductive Centre (MAC), Hospital Canselor Tuanku Muhriz, Pusat Perubatan Universiti Kebangsaan Malaysia (HCTM, PPUKM). The data were analysed using the descriptive statistics technique using the SPSS version 22 computer software. The findings of the study show that the mean score for the causes of stress among infertile women is at a low level (mean=1.96). Hence, the emotional stress among infertile women could be overcome well. Nevertheless, there are several reasons for emotional stress that require for attention such as the stress caused by the enquiries often posed by their relatives about their offspring (mean=3.03), enquiries posed by their friends (mean=2.88), and the feeling of jealousy towards the lives of couples blessed with offspring (mean=2.74). This study helps infertile Muslim women to identify the causes of their emotional stress as well as to find the methods in overcoming them in accordance with the teachings of Islam. Through this, infertile women will still have the positive emotion in attaining peace in their souls and happiness in their lives.